The relationship between pro-innovation organizational climate and innovative work behavior: A study among the knowledge workers of the knowledge intensive business services in Malaysia - Yeoh, Khar Kheng (UUM College of Business, 2012)
This study was conducted to investigate the relationship between pro-innovation organizational climate and innovative work behavior among the knowledge workers of the knowledge intensive business services in Malaysia.The innovative work behavior has a central role in the development of knowledge-intensive business services in Malaysia. It was previously reported that pro-innovation organizational climate to have a significant relationship with innovative work behavior of employees in various business sectors.However, not all support the notion that organizational climate correlates with innovative work behavior.Some of the researchers concluded the relationship is rather weak.This makes it even more interesting to include organizational climate in the research framework of the model of innovative work behavior in Malaysia.A quantitative method was utilized and data were collected using mail survey.A total of 1520 questionnaires was distributed and 310 deemed usable for analysis using SPSS, resulted in 20.6 % response rate.The results revealed that there was a significant relationship between pro-innovation organizational climates with the innovative work behavior of knowledge workers.Discussions of the results and its implications are discussed.